Self-Limiting OX513A Aedes aegypti Demonstrate Full Susceptibility to Currently Used Insecticidal Chemistries as Compared to Indian Wild-Type Aedes aegypti - Prabhakargouda B. Patil; Kevin J. Gorman; Shaibal K. Dasgupta; K. V. Seshu Reddy; Shirish R. Barwale; Usha B. Zehr (Psyche: A Journal of Entomology)
OX513A Aedes aegypti is a genetically engineered strain carrying a self-limiting gene. Studies in several countries have shown the effectiveness of the strain at reducing pest Aedes aegypti populations. As a component of biosafety assessments relevant to Indian environments, OX513A and two Indian wild-type Ae. aegypti strains (from Aurangabad and Delhi) were tested for susceptibility to a range of commonly used insecticides in India, such as dichlorodiphenyltrichloroethane (DDT), malathion, deltamethrin, and permethrin using World Health Organization (WHO) testing kits and following WHO standard test procedures. Knockdown times (KDT) for all compounds were determined separately for male and female adults of the three mosquito strains. Results indicated that adults of OX513A, Aurangabad, and Delhi strains were resistant to DDT, yielding mortality rates of 90.9, 87.4, and 44.4% and 70.1, 3.0, and 6.0% for male and female adults, respectively. In contrast, adults of all three strains were found to be susceptible to malathion, deltamethrin, and permethrin, exhibiting mortalities between 98 and 100%. The magnitudes of susceptibility, based on the KDT50 values, were greater in the OX513A strain, as compared to wild-type strains of Ae. aegypti for all insecticides tested. The results confirm that, aside from historical resistance to DDT, OX513A has retained full sensitivity to these commonly used compounds and exhibits responses akin to those of susceptible Indian wild-type strains.